2017
DOI: 10.1007/s00405-017-4848-5
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal and tongue exercises (myofunctional therapy) for snoring: a systematic review and meta-analysis

Abstract: This systematic review demonstrated that myofunctional therapy has reduced snoring in adults based on both subjective questionnaires and objective sleep studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 21 publications
0
23
0
6
Order By: Relevance
“…Renewed interest for myofunctional therapy was garnered with a series of randomized control trials and cohort studies investigating the role of oropharyngeal exercises, speech therapy, myofascial reeducation, and oronasal rehabilitation for adults and children with sleep‐disordered breathing. Furthermore, a more recent series of meta‐analysis, review articles, books, commentaries, and position statements have catapulted myofunctional therapy to the forefront of the attention within dental and medical communities, albeit not without criticism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renewed interest for myofunctional therapy was garnered with a series of randomized control trials and cohort studies investigating the role of oropharyngeal exercises, speech therapy, myofascial reeducation, and oronasal rehabilitation for adults and children with sleep‐disordered breathing. Furthermore, a more recent series of meta‐analysis, review articles, books, commentaries, and position statements have catapulted myofunctional therapy to the forefront of the attention within dental and medical communities, albeit not without criticism.…”
Section: Discussionmentioning
confidence: 99%
“…Orofacial myofunctional therapy (also known as orofacial myology) has been used for many years to repattern maladaptive oral habits (such as prolonged thumb‐sucking, nail biting, tongue thrusting, and open‐mouth at rest posture) among other objectives . More recently, myofunctional therapy has been demonstrated as a potentially effective treatment option for sleep‐disordered breathing . However, restricted tongue mobility may interfere with the goals and limit the efficacy of myofunctional therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Estos resultados han sido confirmados en diversas series de pacientes con SAHOS, resumidos en un reciente metaanálisis [13][14][15] . Otras ventajas descritas en la respuesta a la TMO son la reducción en 30% a 51% la intensidad y frecuencia de los ronquidos 16,17 , y una mejor adherencia al uso de CPAP cuando se la indica como terapia coadyuvante 18 . Diaféria y cols demostraron que los pacientes con SAHOS tratados con TMO más CPAP tenían una mayor mejoría en los parámetros de calidad de vida respecto a aquellos pacientes tratados sólo con CPAP 19 .…”
Section: Discussionunclassified
“…protruding the tongue, 8 lifting the tongue, 9 moving the tongue in different directions, 10 pressing the tongue against bony and soft tissue structures within the oral cavity, 10 sucking the tongue against the palate, 10 moving the tongue to the right and left over the upper incisor teeth, 11 and other tongue movements with or without external against resistance. 10 Some authors have shown the effectiveness of myofunctional therapy in reducing snoring and sleep apnoea/hypopnoea in children. 10,12,13 One study 14 Tongue training not only induces changes at muscle levels, but also elicits neuroplastic changes in the motor cortex.…”
mentioning
confidence: 99%
“…10 Some authors have shown the effectiveness of myofunctional therapy in reducing snoring and sleep apnoea/hypopnoea in children. 10,12,13 One study 14 Tongue training not only induces changes at muscle levels, but also elicits neuroplastic changes in the motor cortex. 9,[16][17][18] Studies showed that tongue-protrusion training, 16 as well as tongue-lift training, 9 induced significant changes in the motor threshold of the tongue musculature and in the amplitude of the motor-evoked potentials elicited by transcranial magnetic stimulation.…”
mentioning
confidence: 99%